Anunciando a desgraça: o conceito de áte e o coro na tragédia de Ésquilo - Rodrigues, Marco Aurélio (2020)
The chorus in Greek tragedy has always been considered an important element of dramatic composition. Also, especially in the esquilian period, it was one of the essential parts of the representation, manifesting itself as the voice of the people who revealed and inquired the characters about the events, the information and the situations that happened before him. In Aeschylus, particularly, the chorus plays a curious role, as it is also responsible for citing, in most instances of all the author's remaining tragedies, the concept of, whose definition ranges from a mere clouding of ideas to even the consummate misfortune itself. Thus, the present paper, supported above all by the ideas proposed by Doyle (1984), analyzes some passages in which this fact occurs and, in addition, the possible movements that make a complex notion of Greek thought appear more often in the lyrical parts of tragedies.